Ankersmit houdt toezicht in leeszaaltje van Marxistische Arbeidersschool. Copie van origineel in collectie IIAV
Ankersmit houdt toezicht in leeszaaltje van Marxistische Arbeidersschool. Copie van origineel in collectie IIAV.